Improved Security Architecture For Up Keeping Routing Services on Ad Hoc Networks (International Journal of Engineering and Computer Science, 2017)
Nowadays People’s dependence is increasing on crucial applications and wireless networks for executing anytime and anywhere. The presence of active routing protocols enable ad hoc network forming quickly. WANETs suffer from security attacks and intrusions even under several defense mechanisms. In case of providing both secure options and network procedures, we present SAMNAR, a Survivable Ad hoc and Mesh Network Architecture. Its objective is to provide essential preventive, reactive and tolerant security structures adaptively under damages and disturbances. The purpose of SAMNAR is to design a path selection scheme for Wireless Ad hoc Network routing. Our outcome explains that survivability achieved on routing services even under several damages and intrusions.